Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.4103/0019-5154.91844
|View full text |Cite
|
Sign up to set email alerts
|

Dermatitis herpetiformis, primary hypothyroidism and pituitary mass mimicking macroadenoma regression after treatment with thyroxin, corticosteroids and dapsone

Abstract: We report a case of 15-year-old girl who was diagnosed as a case of pituitary macroadenoma on computed tomography and magnetic resonance imaging (MRI) scans for her complains of diminished vision in the left eye and headache. On investigation she was found to have optic atrophy of left eye and primary hypothyroidism. She was started on thyroxin therapy in October 2008 and planned for transcranial excision of the tumor. Just before the date for planned surgery she developed mildly itchy vesico-bullous rash and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…6,7 There have been few case reports from India, but no study has characterized clinical and histopathological characteristics of Indian DH patients. [11][12][13] De et al reported 14 patients of DH from our center (data of these patients has been included in this study), and suggested DH may not be as uncommon in India as previously thought. 14 Two major reasons for apparent low prevalence of DH in Asians can be more consumption of rice and absence of HLA-DQ2 and DQ8.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…6,7 There have been few case reports from India, but no study has characterized clinical and histopathological characteristics of Indian DH patients. [11][12][13] De et al reported 14 patients of DH from our center (data of these patients has been included in this study), and suggested DH may not be as uncommon in India as previously thought. 14 Two major reasons for apparent low prevalence of DH in Asians can be more consumption of rice and absence of HLA-DQ2 and DQ8.…”
Section: Discussionmentioning
confidence: 62%
“…Dermatitis herpetiformis is a relatively rare disease with high prevalence in Scandinavian countries and in the USA . There have been few case reports from India, but no study has characterized clinical and histopathological characteristics of Indian DH patients . De et al .…”
Section: Discussionmentioning
confidence: 99%